Investigação de estratégias de controle clássicas aplicadas em um conversor CC alimentado por um sistema fotovoltaico - Torres, Gustavo Modesto (Brasil, 2021)
Due to pollution problems and increased demand for renewable energy sources, the generation of electricity by photovoltaic panels has been gaining more and more notoriety . However, this form of generation has some challenges, such as the variation in energy production caused by environmental variables and the low efficiency of solar panels. Thus, this form of energy generation can be applied in a distributed system, which allows different generating sources to be connected to different loads and devices, this set of elements is known as microgrid. In order to enable correct operation of loads and minimize losses in a microgrid in direct current (DC), it is common to use converters. Facing with the challenges, this work proposes the analysis of some microgrid prototypes and using classical control techniques, such as Pole Placement, Diophantine Equation and Ackermann's Formula, to mitigate unwanted oscillations through the insertion of photovoltaic generation.